2005
DOI: 10.1109/jproc.2005.849726
|View full text |Cite
|
Sign up to set email alerts
|

Communication systems for building automation and control

Abstract: Building automation systems (BAS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
176
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 407 publications
(194 citation statements)
references
References 24 publications
1
176
0
5
Order By: Relevance
“…They also facilitate or remote building management as well as improved occupant safety and security (Gill et al, 2009;Newman & Morris, 1994). Building automation systems have a hierarchical structure consisting of field, automation and management layers (Kastner et al, 2005b) as shown in figure 1. The field layer comprises of temperature, humidity, light level, and room occupancy sensors.…”
Section: Building Automation and Home Automation Networkmentioning
confidence: 99%
“…They also facilitate or remote building management as well as improved occupant safety and security (Gill et al, 2009;Newman & Morris, 1994). Building automation systems have a hierarchical structure consisting of field, automation and management layers (Kastner et al, 2005b) as shown in figure 1. The field layer comprises of temperature, humidity, light level, and room occupancy sensors.…”
Section: Building Automation and Home Automation Networkmentioning
confidence: 99%
“…Often they are heterogeneous in the offered communication protocols [11], [2], [6], [12]. Available smart devices are developed for different domains, by different vendors, and have different targeted installation environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, the penetration of home control technology in the general population is still very low, due to a number of obstacles: high initial cost, incompatible protocols and lacking interoperability between systems [1].…”
Section: Introductionmentioning
confidence: 99%